Peran Dinas Pendidikan dan Kebudayaan dalam Program Wajib Belajar 13 Tahun di Kabupaten Kutai Kartanegara - Hanaya Puteri OR; Paisal Akbar; Niken Nurmiyati (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
The 13-Year Compulsory Education Program, officially launched in the 2025/2026 academic year, establishes Early Childhood Education (ECE) as a crucial foundation for improving Human Resources (HR) quality. Kutai Kartanegara Regency implements this program through Regent Regulation Number 16 of 2022 on Pre-School ECE. This study aims to analyze the role of the Kutai Kartanegara Education and Culture Office (Disdikbud Kukar) in executing the program, employing Ryaas Rasyid's theory of governmental roles: regulator, dynamizer, and facilitator. A qualitative descriptive method was employed through interviews, observation, and documentation. The findings reveal that Disdikbud Kukar has carried out its regulatory role through proactive local policy issuance and participatory supervision; its dynamizer role through sustainable parenting programs and multi-channel public outreach, although some parents still undervalue ECE; and its facilitator role through the provision of infrastructure and teacher competence development. This study concludes that strengthening public outreach, ensuring equitable access to ECE services, and improving the quality of facilities and educators are essential to optimizing the 13-Year Compulsory Education Program in Kutai Kartanegara Regency.